TEENAGE FATHERS’ PERSPECTIVES AND EXPERIENCES: SOCIAL AND ACADEMIC IMPACT OF EARLY PARENTHOOD IN ESWATINI (NAU Journal of Technology and Vocational Education, 2026)
Despite rising teenage pregnancy rates affecting both boys and girls, most interventions focus exclusively on girls while the voices of boys remain unheard. This study delves into the perceptions of adolescent males who became fathers while enrolled in secondary school in the Manzini Region, Eswatini. Through interviews, the research explores the impacts of teenage pregnancy on their social and academic lives, identifies factors contributing to their actions and seeks solutions from their perspective. This study employed a descriptive research design through a qualitative approach. 'Twenty adolescent males from secondary schools in the Manzini Region were purposively selected using convenience sampling. Semi-structured interviews and focus groups were used to generate data. Framework analysis was used to analyse data. Findings reveal peer pressure, alcohol, lack of parental guidance and exposure to pornography as key drivers behind teenage pregnancy. The study further highlights the unintended consequences faced by boys, including school dropouts, parental disapproval, stress, depression, academic decline and regret. Recommendations advocate for government initiatives, such as training teachers on comprehensive sex education and providing funding for extracurricular activities like sports, to empower teenagers and prevent future pregnancies.
Keywords: teenage fathers; fatherhood; teenage pregnancy; family, social isolation